Assignment of spin and parity to states in the nucleus Â¹â ¹â ¶T1 - Uwitonze, Pierre Celestin (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2015)
This work presents a study of high-spin states in the nucleus Â¹â ¹â ¶Tl via Î³-spectroscopy. Â¹â ¹â ¶Tl was produced via the Â¹â ¹â ·Au(â ´He,5n) Â¹â ¹â ¶Tl reaction at a beam energy of 63 MeV. The Î³-Î³ coincidence measurements were performed using the AFRODITE Î³-spectrometer array at iThemba LABS. The previous level scheme of Â¹â ¹â ¶Tl has been extended up to an excitation of 4071 keV including 24 new Î³-ray transitions. The spin and parity assignment to levels was made from the directional correlation of oriented nuclei (DCO) and linear polarization anisotropy ratios. An analysis of the B(M1)/B(E2) ratios was found to be consistent with the configuration of Ï€hâ‚‰/â‚‚â™ viâ‚ â‚ƒ/â‚‚ for the ground state band. Although no chiral band was found in Â¹â ¹â ¶TI and Â¹â ¹â ¸TI.
Keywords: Nuclear spin; Particles (Nuclear physics) -- Chirality